2006
DOI: 10.1111/j.1574-6941.2006.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial competition between a bacteriocin-producing and a bacteriocin-negative strain of Streptococcus bovis in batch and continuous culture

Abstract: A bacteriocin-producing Streptococcus bovis strain (HC5) outcompeted a sensitive strain (JB1) before it reached stationary phase (pH 6.4), even though it grew 10% slower and cell-free bovicin HC5 could not yet be detected. The success of bacteriocin-negative S. bovis isolates was enhanced by the presence of another sensitive bacterium (Clostridium sticklandii SR). PCR based on repetitive DNA sequences indicated that S. bovis HC5 was not simply transferring bacteriocin genes to S. bovis JB1. When the two S. bov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Clostridium sticklandii SR is more sensitive to bovicin HC5 than S. bovis JB1 (Mantovani & Russell, 2003), but coculture experiments indicated that S. bovis JB1 was inhibited by S. bovis HC5 if the pH was 6.7 (Xavier & Russell, 2006), a pH where little potassium efflux is seen. Breukink and his colleagues (Breukink et al , 2003; Martin & Breukink, 2007) indicated that that nisin had two different activities, pore formation and a direct inhibition of peptidoglycan formation via its interaction with lipid II.…”
Section: Discussionmentioning
confidence: 99%
“…Clostridium sticklandii SR is more sensitive to bovicin HC5 than S. bovis JB1 (Mantovani & Russell, 2003), but coculture experiments indicated that S. bovis JB1 was inhibited by S. bovis HC5 if the pH was 6.7 (Xavier & Russell, 2006), a pH where little potassium efflux is seen. Breukink and his colleagues (Breukink et al , 2003; Martin & Breukink, 2007) indicated that that nisin had two different activities, pore formation and a direct inhibition of peptidoglycan formation via its interaction with lipid II.…”
Section: Discussionmentioning
confidence: 99%